Graphene oxide on microbially induced calcium carbonate precipitation. (November 2019) - Tang, Guowang; Wang, Guihe; An, Yuxiu; Zhang, Haonan
Abstract: The improvement of microbial induced calcium carbonate precipitate (MICP) using additives has attracted much attention due to its great influence on the quality of precipitate. In this paper, graphene oxide (GO) was used as an additive to induce CaCO3 precipitate. Using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), the effects of GO on immobilization of bacteria, CaCO3 crystals and the consolidation of sand was studied. The addition of GO caused the rapid growth and the larger size of the CaCO3 crystals. Additionally, the morphology of the rhombohedral crystals was unchanged. The precipitation capability of CaCO3 during the MICP process was improved significantly. X-ray diffraction (XRD) noted that stable calcite was formed during the CaCO3 precipitate process with GO, compared to calcite and vaterite formed. More importantly, the unconfined compressive strength of the consolidated sand was significantly enhanced. These results show that GO has outstanding properties. Graphical abstract: Image 1 Highlights: .An effective graphene oxide was used during the MICP process. .Bacterial were immobilized in the present of graphene oxide. .Graphene oxide exhibited outstanding CaCO3 precipitate ability. .Graphene oxide accelerated the deposition of Ca 2+ . .The unconfined compressive strength of the consolidated sand samples were improved with graphene oxide.